The liophilization process in raw human milk and after pasteurization for glutamine analysis - S.S, Souza; J.A, Silva; C.A.O, Ricart; J.S.F, Almeida; C, Caporossi (Seven Editora, 2023)
Objective: to evaluate the concentration of the amino acid glutamine in breast milk, in the mature lactation stage and after its pasteurization and lyophilization process.  Methods: Twenty-six postpartum women were initially recruited, of which 18 were eligible, 8 were excluded, and 10 postpartum women participated. Each sample of 100ml of milk in the mature stage (15th day of puerperium) was collected individually at each address. The samples were divided into two fractions of 50 ml each, one fraction intended for measurement of glutamine in the stage of lyophilized mature breast milk (LHML) and the other fraction for measurement in lyophilized and pasteurized mature breast milk (LHMPL). Results: the average age of the mothers was 22 to 34 years old, the BMI of 26.79 Kg/m2, the gestational age of 38.95 weeks, normal delivery occurred in 60% of the patients the profile of the newborns 70% female and 30% male with an average weight of 3.29 kg and height of 51.85 cm. The concentration of glutamine in the LHML group was 1.80 μMOL + 0.33 and in the LHMPL group it was 1.93 μMOL + 0.44 (p > 0.05).Conclusion: pasteurization and lyophilization processes will not change the concentration of glutamine in breast milk. DOI: https://doi.org/10.56238/colleinternhealthscienv1-043